Girl in the cellar: a repeated cross-sectional investigation of belief in conspiracy theories about the kidnapping of Natascha Kampusch - Stieger, Stefan; Gumhalter, Nora; Tran, Ulrich S.; Voracek, Martin; Swami, Viren (Frontiers in Psychology, 2013)
The present study utilized a repeated cross-sectional survey design to examine belief in conspiracy theories about the abduction of Natascha Kampusch. At two time points (October 2009 and October 2011), participants drawn from independent cross-sections of the Austrian population (Time Point 1, N = 281; Time Point 2, N = 277) completed a novel measure of belief in conspiracy theories concerning the abduction of Kampusch, as well as measures of general conspiracist ideation, self-esteem, paranormal and superstitious beliefs, cognitive ability, and media exposure to the Kampusch case. Results indicated that although belief in the Kampusch conspiracy theory declined between testing periods, the effect size of the difference was small. In addition, belief in the Kampusch conspiracy theory was significantly predicted by general conspiracist ideation at both time points. The need to conduct further longitudinal tests of conspiracist ideation is emphasized in conclusion.